Strength of Pulvertaft modifications: tensile testing of porcine flexor tendons. (October 2019) - Strandenes, Eivind; Ellison, Peter; Mølster, Anders; Gjerdet, Nils R.; Moldestad, Irene O.; Høl, Paul J.
The aim of the study was to present two new modifications of the Pulvertaft weave, allowing a higher number of weaves without the need for a longer overlap. The mechanical properties were measured and compared with the traditional technique. Forty-five pairs of porcine flexor tendons were randomized to a Pulvertaft repair with three weaves, a Double Pulvertaft and Locking Pulvertaft repairs. In the last two repairs one of the tendons in each repair was split in two before weaving. A difference in the maximum stiffness was observed between the three groups ( p  = 0.024). All repairs failed by the sutures being sheared through the tendons splitting the tendon fibres longitudinally. The two modifications were both stronger than the Pulvertaft weave and provide an alternative when a strong connection is needed and a longer overlap is impossible.